THE USE OF DUOLINGO APPS TO IMPROVE STUDENTS’ VOCABULARY MASTERY OF SMP NEGERI 4 PALU - Achmad, Putri Fatimah; Mukrim, Mukrim; Anggreni, Afrillia (Tadulako University, 2025)
The purpose of this research is to find out whether the use of Duolingo apps as media in learning activity can improve students’ vocabulary of mastery or not. This research used pre-experimental design. The sample was 31 seventh grade students from SMP Negeri 4 Palu. Duolingo application was used as an instrument in this research. All the data gained in this research were analyzed by using Arikunto’s formula. The result shows that the use of Duolingo Application can improve students’ vocabulary mastery. Based on the calculation, the post-test mean score was 73,23 while the pre-test was 63,39. The result of statistical analysis showed that the value of t-counted (212,31) was higher than the value of t-table (1.697) with 0.05 level of significance of 30 (31-1) degree of freedom (df). The result indicated that the use of Duolingo application can improve students’ vocabulary mastery of the seventh grade students SMP Negeri 4 Palu.